Cinejornal Brasileiro: a documentação do esporte no Estado Novo em comparação com a estética de Leni Riefenstahl - Clara Alves Teixeira (2011)
This dissertation has as objective the study of movies of Cinejornal Brasileiro, produced by Department of Press and Propaganda, during New State. Knowing that sports have always been used by several governments as union element, this study focuses on movies with sports themes and also about the improvement of physical indexes of the Brazilian people. The cinema was an important instrument used for approval of the authoritarian regime in force in Brazil between 1937 and 1945. Through this, Getúlio Vargas could spread the physical and comportamental ideal of the new Brazilian man, based on a esthetic wich remembers, at some points, that used by Leni Riefenstahl on nazi propaganda films.